The Analysis of Pressure Drop on RL 014 for Condensate Disposal on Geothermal Pipe Line - Rial Dwi Martasari; Trias Puji Lestari (Penerbitan Universitas Trisakti, 2020)
Geothermal energy from the Earth's magma is manufactured in the form of hot steam. On the process of transmission of steam in the Pipe Line, there are various problems such as condensation in the steam. Condensation can cause problems such as pressure drop. The formation of condensate gives a negative impact on production activities both in the pipeline or power plant, thus condensate formed in pipelines should be disposed of via the blow down or steam trap. Due to a large number of steam pipelines in the DW area then to do an analysis of pipelines in order to prioritize the disposal of condensate in the pipe more prone formed condensate. DW Area special analysis was not done against condensation and the number of condensates that are formed so as to indicate the occurrence of condensation done with regular analysis pressure drop in the pipeline. The results of the analysis of the pipeline must first and more frequently carried out disposal of condensate on the RL 014 based on pressure drop highest is line DW 14 a and DW 67, next line DW 18 and 17, and the last is the line 11 and 14 b DW. The condition of the steam trap is also noteworthy if the steam trap leak then it can lower the temperature in the pipe. The drop in temperature in the pipeline will accelerate the condensation, the results of the analysis there is a steam trap leaked is 401.00.17.ST19 and 401.00.05.ST14 . Steam trap leaked that needs to be done to combat the most. The production of steam RL 014 per day was able to donate a 52.52% or about 73.5 MW of the total needs of PLTP (geothermal power plant) 140 MW per day.